AI Usage in the Classroom: Understanding and Mitigating Cognitive Offloading - Atti Yudiernawati; Soetam Rizky Wicaksono; Tavip Dwi Wahyuni (Journal of Educational Studies, 2026)
The integration of artificial intelligence (AI) in higher education has significantly transformed how students complete academic tasks, particularly in writing and analysis. This research aims to examine the impact of AI usage on students’ self-efficacy by considering cognitive offloading as an underlying mechanism. The research was conducted in an Information Systems program at a university in Malang, Indonesia, involving two classes: Digital Transformation (21 students) and Financial Technology (17 students). AI tools such as ChatGPT, Gemini, and Consensus were used to support writing, analysis, and referencing processes. Data were collected through questionnaires at the midterm and final stages, supported by focus group discussions with selected students. The results show that, at the initial stage, most students perceived AI as a tool that simplifies tasks, leading to reduced cognitive effort and increased dependency. This indicates the presence of cognitive offloading, where students rely on AI instead of engaging in deep thinking. However, after the implementation of structured learning strategies, including direct review, oral assessment, and continuous feedback, approximately half of the students demonstrated a shift toward more active cognitive engagement. They began to prioritize reasoning and validation of AI-generated outputs. Nevertheless, a small group of students remained dependent on AI, while others showed transitional behavior. This research concludes that AI can both weaken and strengthen students’ self-efficacy, depending on how it is integrated into the learning process. Cognitive offloading is not an inevitable outcome but can be controlled through appropriate instructional design. Therefore, lecturers play a critical role in ensuring that AI functions as a supportive tool rather than a replacement for cognitive processes.